Faculty Of Hotel & Tourism Management a study of employee fulfillment towards loyalty in hotel industry / Hassrul Hafize Abdul Halim Hafiz & Mu’az Mohd Radzi - Abdul Halim Hafiz, Hassrul Hafize; Mohd Radzi, Mu’az (2018)
Job loyalty in a simple word is defined as the action of employees staying in one job without hopping to another job for a long time. Management have to come out with ideas on how to retain their employees in order to save budget from recruiting new employees. This study is about the employee fulfilments towards loyalty in Hotel Industry. This research is conducted to study about the relationship between employee loyalty and the three variables which are compensation, job security and workplace environment. According to previous studies conducted, there is a significant relationship between these variables and the employee loyalty. In this research, researchers have conducted this study by using secondary data which is collecting data from journals, articles, books and other reliable sources. Furthermore, there are also few suggestions proposed in the last part of this research for future researchers to conduct this research and have a more accurate outcome.